Differences in neural connectivity between the substantia nigra and ventral tegmental area in the human brain - Kwon, Hyeok Gyu; Jang, Sung Ho (Frontiers in Human Neuroscience, 2014)
Objectives: Many animal and a few human studies have reported on the neural connectivity of the substantia nigra (SN) and the ventral tegmental area (VTA). However, it has not been clearly elucidated so far. We attempted to investigate any differences in neural connectivity of the SN/VTA in the human brain, using diffusion tensor imaging (DTI). Methods: Sixty-three healthy subjects were recruited for this study. DTIs were acquired using a sensitivity-encoding head coil at 1.5T. Connectivity was defined as the incidence of connection between the SN/VTA and each brain regions in the brain. Results: The connectivity of SN was higher than that of the VTA. This included in the primary motor cortex, primary somatosensory cortex, premotor cortex, prefrontal cortex, caudate nucleus, globus pallidus, putamen, nucleus accumbens, temporal lobe, amygdala, pontine basis, occipital lobe, anterior and posterior lobe of cerebellum, corpus callosum, and external capsule (p< .05). However, no significant differences were observed in the red nucleus, thalamus, pontine tegmentum, and medial temporal lobe between the SN and VTA (p>.05). Conclusions: We found the differences in neural connectivity of the SN/VTA in the human brain. The method and results of this study can provide useful information for clinicians and researchers in neuroscience, especially who work for Parkinson’s disease and patients with brain injury.